2008
DOI: 10.1097/pas.0b013e3181659791
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hepatic Malignant Fibrous Histiocytoma

Abstract: Primary hepatic malignant fibrous histiocytoma (MFH) is a rare entity with ill-defined clinicopathologic characteristics. We present the largest series to date (7 cases) of primary hepatic MFH, a systematic review of 27 cases published in the English literature, and an analysis of prognostic factors including ezrin expression. The 2 men and 5 women in our series were 34 to 80 years old (average 61 y) and presented with abdominal pain (6/7), systemic symptoms of low-grade fever, malaise, anorexia and weight los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 43 publications
2
14
1
Order By: Relevance
“…In the previous study in the English literature, patients were all older than 34, whereas in our study it is found that there are also 4 patients younger than 15 years old, including 1 boy and 3 girls, suggesting that the primary hepatic MFH could also occur among young persons. In addition, in a recent study of 34 cases, Li and colleagues showed that there was no sex predilection in the hepatic MFH[27], while in our study, 50 of 76 patients in China were men, with a male to female ratio of 1.9:1, suggesting that there might be a slight male predominance for the incidence of this rare malignant tumor. Certainly, these results still waits further confirmed in the future study.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…In the previous study in the English literature, patients were all older than 34, whereas in our study it is found that there are also 4 patients younger than 15 years old, including 1 boy and 3 girls, suggesting that the primary hepatic MFH could also occur among young persons. In addition, in a recent study of 34 cases, Li and colleagues showed that there was no sex predilection in the hepatic MFH[27], while in our study, 50 of 76 patients in China were men, with a male to female ratio of 1.9:1, suggesting that there might be a slight male predominance for the incidence of this rare malignant tumor. Certainly, these results still waits further confirmed in the future study.…”
Section: Discussioncontrasting
confidence: 40%
“…Primary hepatic MFH is exceedingly rare, especially in comparison with MFH of other sites, or with the more common primary malignancies of the liver [2,33]. Since its original description in 1985[5], to date, only 45 cases have been described in the English literature, including recent reports by Li et al [27], Sugitani M et al [28], Kim HS et al [29], Caldeira A et al [30] and Cong Z et al [31]. Among the 45 cases, 8 cases were from China [24-26,31].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, CD-68, KP-1, and α1-antichymotrypsin were positive, conforming to the feature of MFH. [4,9,10] Thus, MFH with margin negative was confirmed pathologically.…”
Section: Discussionmentioning
confidence: 78%
“…[4,9–10] However, the histopathologic concept of MFH including storiform-pleomorphic, myxoid, inflammatory, giant cell, and angiomatoid variants had been eliminated; concomitantly World Health Organization denominated most of the MFH as undifferentiated pleomorphic sarcomas in 2002. [17] …”
Section: Discussionmentioning
confidence: 99%
“…However, as the fever and CRP level dramatically improved after the surgery, the gastric tumors were clearly related to the main complaints. There are reports about cases of UPS and MFH presenting initially with fever [21–23], and reports about cases of MFH producing actively cytokines such as G-CSF [2427]. But.…”
Section: Discussionmentioning
confidence: 99%